2020
DOI: 10.3390/informatics7040042
|View full text |Cite
|
Sign up to set email alerts
|

Usability in Patient-Oriented Drug Interaction Checkers—A Scandinavian Sampling and Heuristic Evaluation

Abstract: Drug interactions are an important source of medical error and a topic of particular interest to patient audiences. Patients must be informed to be able to participate in decision-making affecting their health. This paper explores the availability of drug interaction checkers in Scandinavia and the prevalence and characteristics of usability issues preventing patients from benefiting from them. Drug interaction checkers were sampled and evaluated through heuristic evaluations. Issue-based data were analyzed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This is in line with previous research describing that patients’ sources of drug information and information about DDIs are primarily physicians, pharmacists, relatives, patient information leaflets and online sources [ 44 , 45 , 46 ]. Internationally there are different mobile apps and web pages that provide DDI services to patients, but research regarding patients use of them is limited [ 19 , 20 , 25 ]. Previous studies have shown that patients often have limited knowledge and awareness regarding DDIs [ 38 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with previous research describing that patients’ sources of drug information and information about DDIs are primarily physicians, pharmacists, relatives, patient information leaflets and online sources [ 44 , 45 , 46 ]. Internationally there are different mobile apps and web pages that provide DDI services to patients, but research regarding patients use of them is limited [ 19 , 20 , 25 ]. Previous studies have shown that patients often have limited knowledge and awareness regarding DDIs [ 38 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest that among patients there is a need of “rather diverse but only limited information domains” regarding DDI [ 18 ]. Vingen et al [ 20 ] state that in order for patients to act as decision-makers regarding their own health, we need to empower them with information. The systems conveying this information must be usable in order for empowerment to take place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the study by Vingen et al reports on available DDI website checkers in Scandinavian market [38]. They identified three Norwegian (Interaksjoner.no, Felleskatalogen.no, Legemiddelsok.no), two Danish (Medicinkombination.dk and Interaktionsdatabasen.dk), and one Swedish (Janusmed) service.…”
Section: Key Findings Of Papers Relevant To Rq2mentioning
confidence: 96%
“…The reasons include: perceived complexity of information; fear of creating patient anxiety, which could lead to patients not taking their medication; or increased concerns and unnecessary questions to health care professionals [33]. There are already some apps or services available for patients to check for DDI indicating an existing need or demand among patients [34][35][36][37][38]. However, there is limited knowledge about any effects or if their design or content is appropriate for patients.…”
Section: Introductionmentioning
confidence: 99%